Trade liberalization, Economic Growth and Poverty Level in Nigeria: Vector Auto-regression (VAR) Approach (1980-2009) - Aremo, Aremo (Journal of Economics and Behavioral Studies, 2014)
The paper examines the nexus among trade liberalization, economic growth and poverty level in Nigeria between 1980 and 2009 within the context of multivariate Vector Auto regression (VAR) with a view to establishing the links that exist among the three variables. The data series were also subjected to unit root and co integration tests to examine the properties of the data. The findings that emerged from the analyses showed that the interactions among trade liberalization, economic growth and poverty level suggest that economic growth had a positive impact on trade liberalization in Nigeria within the study period. Also, the interactions among trade liberalization, economic growth and poverty level were weak making the effect of trade liberalization on poverty to be low. This probability portrays the presence of some structural rigidity in the economy capable of preventing the impact of trade liberalization from being fully felt on poverty, particularly through economic growth channel. This suggests the presence of some institutional factors that create inherent problems in the economy that could largely frustrate any valid and sincere trade policies formulated by the government. It is therefore recommended that policy makers should be mindful of the fact that the Nigerian economy is structurally vulnerable; such that for any policy to succeed, the peculiar characteristics of the economy must be factored into the plan and rigorously evaluated for good policy effects.